Дослідження особливостей процесу руйнування агломерату в пристрої барабанного типу - Бочка, В.В.; Сова, А.В.; Двоєглазова, А.В. (Physico-technological Institute of Metals and Alloys, 2023)
An impact assessment of the required magnitude of the applied load energy on the agglomerate has been made using mathematical modeling of the sinter fracture process in a drum type device and an experiment in the physical drum model. It has been established that effective stabilization of agglomerate in the drum takes place in the presence of three characteristic destruction zones with different mechanisms: crushing with the maximum value of shock loads; stabilization of characteristics with minimal formation of trifles by reducing shock loads; providing spherical shapes to the pieces of agglomerate when processed mainly by the energy of abrasion and splitting. The optimum constructional and technological characteristics of the drum are offered.